Life in Death: Addressing Heterotopic Burial Spaces by Re-Introducing Burial Rituals into the Inner-City of Pretoria - Bothma, Cobus (University of Pretoria, 2021)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2020.